2018
DOI: 10.1016/j.compstruct.2018.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Size effects in elastic-plastic functionally graded materials

Abstract: We develop a strain gradient plasticity formulation for composite materials with spatially varying volume fractions to characterize size effects in functionally graded materials (FGMs). The model is grounded on the mechanismbased strain gradient plasticity theory and effective properties are determined by means of a linear homogenization scheme. Several paradigmatic boundary value problems are numerically investigated to gain insight into the strengthening effects associated with plastic strain gradients and g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…For example, the extension to metal-based elastic-plastic FGMs is immediate in the absence of plastic-damage coupling, provided that plastic size effects are accounted for [39]. Similarly, the framework can easily accommodate other homogenization schemes, such as those proposed for functionally graded composites integrating carbon nanotubes [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the extension to metal-based elastic-plastic FGMs is immediate in the absence of plastic-damage coupling, provided that plastic size effects are accounted for [39]. Similarly, the framework can easily accommodate other homogenization schemes, such as those proposed for functionally graded composites integrating carbon nanotubes [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the information available is the spatial variation of the volume fractions of constituent materials, which is provided as input to the production technique [16]. The macroscopic material property variation does not tend to mirror the volume fraction profile, but one can estimate the former from the latter by using homogenization laws [17]. However, the micromechanical assumptions upon which these theoretical mixing laws are built may hinder an accurate characterization of the macroscopic variation of material properties.…”
Section: Numerical Formulationmentioning
confidence: 99%
“…The effect of material parameters such as constituent volume fraction (Vc), size, shape, particle distribution on the elastoplastic deformations, failure mechanisms, and microstructure heterogeneity of FGMs under quasi-static loading have been widely studied. [13][14][15][16][17][18][19][20][21] For example, Kubair and Lakshmana 22 carried out a numerical study of initiation and growth of damages in layered composites structures with a functionally graded core. The simulation indicated that the energy absorption due to the damage process is modified by the presence of the functionally graded core, Moreover, Gunes et al 23 analyzed the elastic and elastoplastic behavior of functionally graded circular plates under low-velocity impact loading using experimental and computational techniques.…”
Section: Introductionmentioning
confidence: 99%